2017
DOI: 10.1177/0264550517699290
|View full text |Cite
|
Sign up to set email alerts
|

A Rapid Evidence Assessment of the effectiveness of prison education in reducing recidivism and increasing employment

Abstract: This is a Rapid Evidence Assessment (REA) of educational programmes delivered within prison. Included in this review are evaluations of vocational, academic, basic skills, accredited and unaccredited educational provision in prison where recidivism and/or employment were measured as outcomes. Initial searches returned 4,304 titles and abstracts. Of these, 28 papers met the criteria for inclusion. Only 18 papers provided sufficient information and robust enough research design to be included in the meta-analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 21 publications
1
26
0
5
Order By: Relevance
“…The United States has the largest prison population in the world; notwithstanding the structural issues facing the criminal justice system, education has been shown to dramatically reduce recidivism rates. Completing an educational program in prison reduces the likelihood of recidivating on average by approximately one-third and suggests a 24 percent increase in the likelihood of getting a job (Ellison et al 2017). These numbers are higher still for students who earn college (rather than high school or GED) degrees.…”
Section: Resultsmentioning
confidence: 99%
“…The United States has the largest prison population in the world; notwithstanding the structural issues facing the criminal justice system, education has been shown to dramatically reduce recidivism rates. Completing an educational program in prison reduces the likelihood of recidivating on average by approximately one-third and suggests a 24 percent increase in the likelihood of getting a job (Ellison et al 2017). These numbers are higher still for students who earn college (rather than high school or GED) degrees.…”
Section: Resultsmentioning
confidence: 99%
“…Various studies stress that increased schooling is a protective factor with respect to antisocial behavior (Casey, 2011;Gomide, Ropelato, & Alves, 2006;Matos, Martins, Jesus, & Viseu, 2015;Silva & Bazon, 2015;Silva, Cianfl one, & Bazon, 2016). In a meta-analysis of 18 studies concerning the role of prison education aimed at rehabilitating adult inmates, Ellison, Szifris, Horan, and Fox (2017) indicated that participating in educational activities reduces the probability of recidivism by approximately one-third, while producing a 24% increase in the inmate's likelihood of fi nding a job. Preto, vol.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 50% of state prisons offer vocational services to support employment opportunities after re-entering the community [ 9 ]. Although few vocational rehabilitation services delivered in prisons translate into promising reductions in recidivism [ 10 ], even fewer have been rigorously evaluated with a randomized controlled design [ 11 ]. Thus, there are promising vocational rehabilitation services that require further evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…For example, we designed a protocol to evaluate VR-JIT within the individual placement and support model of supported employment services for adults with serious mental illness [ 22 ]. Given the low levels of employment among returning citizens and lack of evidence-based vocational rehabilitation services within prison settings [ 8 , 11 ], the current study will investigate VR-JIT as an enhancement to existing vocational services implemented in two prisons in the State of Michigan called the Vocational Villages. The Vocational Villages provide an immersive educational community using virtual reality, robotics, and other technologies to support returning citizens becoming employable tradespeople [ 23 ].…”
Section: Introductionmentioning
confidence: 99%